Parataxis, Hypotaxis, Style and Translation (Journal of the College of Basic Education, 2022)
Parataxis and hypotaxis are compound words that refer to two stylistic devices. They involve the arrangement of propositions one after the other in such a way that goes in line with the role that each proposition plays in speech or writing.It is the purpose of this study to shed some light on these two devices by explaining the way in which they differ from each other, and what tools are used to achieve them. The study also shows a sort of comparison between parataxis and hypotaxis in terms of preference of usage in English and Arabic. Moreover, some problems that may arise in translation are being reviewed. The paper ends up with some conclusions that may be of use to those interested in this field.